North American thinking on international relations - Parodi Trece, Carlos A. (1995)
This article looks at US foreign relations. The changes that occurred at the end of the 1980s brought new perspectives on theory into discussion, with realism and neorealism at the heart of the debate. The author goes on to dissect different outlooks on the redistribution of world power and the role that will fall to the US in the future, stemming from an analysis of its foreign policy in the new international environment. The author also turns his attention to the new role of international organizations, military and economic power, as well as democracy and human rights.